Antiguos actores de un nuevo régimen: indígenas y afrodescendientes en el Paraguay de la Independencia - Ignacio Telesca; Guillermo Wilde (Journal de la Société des Américanistes)
Ancient actors for a new regime: Indigenous people and Afrodescendants in Paraguay during the Independence. This paper explores the characteristics of the process of independence on the region of Paraguay focusing in the social dynamics of the Indigenous and African descent populations. The first part analyzes responses of the villages to the discourse of the Buenos Aires Junta Government. We suggest that said discourse, even though at a first glance seems to be oriented to define a « new political actor », actually expressed an important level of continuity with the directions of the Colonial State in its late phase. In this context, the villages subject to the Asunción jurisdiction took a political path different to those under the influence of Buenos Aires, conditioned by the demographic and territorial situation that prevailed in the region. The second part provides details about the characteristics of this situation and its evolution since the previous decades that correspond to the end of the colonial period. It is our contention that in those previous decades can be found some clues to understand the meaning of the responses indigenous and African descent population adopted toward the processes of independence in Paraguay and, ironically, their rapid vanishing from the official records